A LITERARY REVIEW ON SAMPRAPTI OF PANDU ROGA. - Sarkar, Arpita; Baberwal, Avinash; Maity, Debnarayan (International Research Journal of Ayurveda & Yoga, 2019)
In my view Pandu is such a disease which is probably one of the 5 of most common diseases, have great prevalence with almost 30% of world population affected, large capacity to influence other health factors but most neglected in comparison to those. The clinical condition of this disease has a lot of similarities with the sign and symptoms of Anaemia. Although it is commonest where there is malnutrition or nutritional deficiency but it is also found in overnourished people. But pathogenesis of Anaemia and Samprapti of Pandu are not explained in same format. So, in this condition we tried to find out the point of similarity in explanation of pathogenesis of Pandu in Ayurvedic and modern medicinal system. Because in Ayurvedic classics Pandu is mentioned as a Santarpanjanya vikara i.e. a disease due to overnutrition but not a disease due to Apatarpan i.e. malnutrition.